RNA sequencing confirms similarities between PPI‐responsive oesophageal eosinophilia and eosinophilic oesophagitis. Issue 2 (4th June 2018) - Peterson, K. A.; Yoshigi, M.; Hazel, M. W.; Delker, D. A.; Lin, E.; Krishnamurthy, C.; Consiglio, N.; Robson, J.; Yandell, M.; Clayton, F.
Summary: Background: Although current American guidelines distinguish proton pump inhibitor‐responsive oesophageal eosinophilia (PPI‐REE) from eosinophilic oesophagitis (EoE), these entities are broadly similar. While two microarray studies showed that they have similar transcriptomes, more extensive RNA sequencing studies have not been done previously. Aim: To determine whether RNA sequencing identifies genetic markers distinguishing PPI‐REE from EoE. Methods: We retrospectively examined 13 PPI‐REE and 14 EoE biopsies, matched for tissue eosinophil content, and 14 normal controls. Patients and controls were not PPI‐treated at the time of biopsy. We did RNA sequencing on formalin‐fixed, paraffin‐embedded tissue, with differential expression confirmation by quantitative polymerase chain reaction (PCR). We validated the use of formalin‐fixed, paraffin‐embedded vs RNAlater‐preserved tissue, and compared our formalin‐fixed, paraffin‐embedded EoE results to a prior EoE study. Results: By RNA sequencing, no genes were differentially expressed between the EoE and PPI‐REE groups at the false discovery rate (FDR) ≤0.01 level. Compared to normal controls, 1996 genes were differentially expressed in the PPI‐REE group and 1306 genes in the EoE group. By less stringent criteria, only MAPK8IP2 was differentially expressed between PPI‐REE and EoE (FDR = 0.029, 2.2‐fold less in EoE than in PPI‐REE), with similar results by PCR. KCNJ2, which was differentially expressed in a prior study, was similar in the EoE and PPI‐REE groups by both RNA sequencing and real‐time PCR. Conclusion: Eosinophilic oesophagitis and PPI‐REE have comparable transcriptomes, confirming that they are part of the same disease continuum.